Ethical Leadership as a Strategic - Jana Sandra; Baby Poernomo; Rafika Ludmilla; Rohani Lestari Napitupulu (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines ethical leadership as a strategic imperative in contemporary organizations, particularly within environments shaped by digital transformation and artificial intelligence (AI). While AI-driven systems offer significant advantages in efficiency and decision-making, organizations continue to face ethical challenges related to accountability, transparency, bias, and governance. The main problem addressed in this study is the limited integration of ethical leadership frameworks into strategic management and AI governance, where ethics is often treated as a peripheral value rather than a strategic capability. Accordingly, this study aims to reposition ethical leadership as a core strategic driver that guides organizational decision-making and responsible technology adoption. Using a qualitative analytical approach, this research synthesizes peer-reviewed literature on ethical leadership, strategic management, and AI governance through thematic and comparative analysis. The method focuses on identifying strategic patterns, governance mechanisms, and leadership roles that link ethical principles with long-term organizational objectives. The findings indicate that ethical leadership functions as a foundational strategic capability by aligning organizational values with strategic actions, strengthening governance structures, and enhancing stakeholder trust in AI-enabled decision systems. Ethical leadership is shown to play a critical role in mediating ethical risks associated with AI, such as opacity and accountability gaps, while supporting responsible innovation and organizational legitimacy. The synthesis of findings demonstrates that ethical leadership extends beyond individual moral behavior and operates at the strategic level through institutionalized policies, governance frameworks, and strategic planning processes.